Physiological and biochemical responses of wheat to synergistic effects of selenium nanoparticles and elevated CO2 conditions - Alsherif, Emad A.; Hajjar, Dina; Aldilami, Mohammad; AbdElgawad, Hamada (Frontiers in Plant Science, 2023)
Elevating CO2 (eCO2) levels will change behavior and the effect of soil fertilizers and nutrients. Selenium NPs (SeNPs) have arisen as an alternative to conventional Se fertilizers to enrich crops. However, it remains unclear whether eCO2 will change the biological effects of soil SeNPs on plant growth and metabolism. The current study aimed to shed new light on the interactive impacts of eCO2 and SeNPs on wheat plants. Accordingly, the attempts were to reveal whether the application of SeNPs can modulate the eCO2 effects on wheat (Triticum aestivum L.) physiological and biochemical traits. With this goal, a pot experiment was carried out where the seeds were primed with SeNPs and plants were grown under two levels of CO2 concentrations (ambient CO2 (aCO2, 410 μmol CO2 mol−1; and eCO2 (710 μmol CO2 mol−1)) during six weeks after sowing. Although SeNPs+eCO2 treatment resulted in the highest accumulation of photosynthetic pigment content in leaves (+49-118% higher than control), strong evidence of the positive impacts on Rubisco activity ( +23%), and stomatal conductance ( +37%) was observed only under eCO2, which resulted in an improvement in photosynthesis capacity (+42%). When photosynthesis parameters were stimulated with eCO2, a significant improvement in dry matter production was detected, in particular under SeNPs+eCO2 which was 1.8 times higher than control under aCO2. The highest content of antioxidant enzymes, molecules, and metabolites was also recorded in SeNPs+eCO2, which might be associated with the nearly 50% increase in sodium content in shoots at the same treatment. Taken together, this is the first research documenting the effective synergistic impacts of eCO2 and SeNPs on the mentioned metabolites, antioxidants, and some photosynthetic parameters, an advantageous consequence that was not recorded in the individual application of these treatments, at least not as broadly as with the combined treatment.